Military and Control of Land Resources? Conflict TNI and Magelang City Government - Hendy Setiawan (Journal of Government and Political Issues, 2021)
The military's involvement in power and land ownership often leads to conflicts, both vertically and horizontally. According to the Agrarian Reform Consortium's records in 2020, agrarian conflicts involving military personnel during the Covid-19 pandemic were relatively stagnant. This paper aims to explore the conflict between the TNI Akmil Magelang and the Magelang City Government. The method used in this study uses a descriptive qualitative approach. Data collection techniques in this study using observation and documentation techniques and processing research data using the stages of data presentation, verification, and concluding. This study uses Pondy's (1967) theory regarding the stages of conflict as an analytical tool. The results show that the military conflict over land control with the city government has occurred since 1985. However, this conflict has not yet found common ground. The peak of the conflict occurred in mid-August 2020 when the TNI put up a sign at the mayor's office complex. The TNI gave an ultimatum to the Magelang City Government to leave or compensate for land assets. The development of the conflict is currently heading towards conflict resolution. However, it does not mean that in the end the conflict resolution can be found. This departs from the historical record where this conflict has been going on for a long time, and various parties as mediators are involved. However, the conflict continues to roll on and at any time can explode again in public.